2015
DOI: 10.1186/s12889-015-2389-7
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of hepatitis B and poor knowledge on hepatitis B and C viral infections among barbers: a cross-sectional study of the Obuasi municipality, Ghana

Abstract: BackgroundBarbers, while shaving, may be accidentally exposed to the blood and bodily fluids of their customers increasing their risk of contraction of HBV and HCV infections. Hence, this study aimed at examining the prevalence and knowledge of barbers on HBV and HCV infections in the Obuasi municipality of Ghana.MethodsA work place based cross-sectional study was conducted from January to April 2015 at the Obuasi municipality in the Ashanti Region of Ghana. Two hundred (200) barbers were conveniently recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 14 publications
(20 reference statements)
5
42
3
Order By: Relevance
“…This HCV prevalence was different from other studies among beauticians in Ghana (0.5%), 30 Brazil (0.8%), 10 Izmir, Turkey (0.9%), 29 Morocco (1.7%), 28 Teheran, Iran (2.0%), 25 Sivas, Turkey (2.8%), 37 and Pakistan (6.97%). 38 We may not have had a sufficient sample size to detect HCV infection in a low prevalence population, and we calculated our sample size based on estimating HBV prevalence, not HCV prevalence.…”
Section: Discussioncontrasting
confidence: 47%
“…This HCV prevalence was different from other studies among beauticians in Ghana (0.5%), 30 Brazil (0.8%), 10 Izmir, Turkey (0.9%), 29 Morocco (1.7%), 28 Teheran, Iran (2.0%), 25 Sivas, Turkey (2.8%), 37 and Pakistan (6.97%). 38 We may not have had a sufficient sample size to detect HCV infection in a low prevalence population, and we calculated our sample size based on estimating HBV prevalence, not HCV prevalence.…”
Section: Discussioncontrasting
confidence: 47%
“…Fourteen included studies assessed the awareness of 9,446 Africans in regard to HBV, three studies were conducted in each of Nigeria [61,62,64] , Cameroon [20,40,58] and Ghana [12,15,28] , two in Ethiopia [32,52] , one in each of Kenya, Mozambique and Madagascar [26,57,71] . The oldest among the study included was conducted in 2010 while the newest was conducted in 2016 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Six included studies assessed the awareness of 2,306 Africans in regard to HCV, two studies were conducted in Egypt [74,79] and one in each of Ghana [15] , Mozambique [26] , Ethiopia [32] and Madagascar [71] . The oldest among the study included was conducted after 2010 while the newest was conducted in 2015 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Healthcare providers should be educated strictly to follow infection control measures because they can be victims or source of disease transmission. Comparatively, a recent study identified that the modes of disease transmission were unknown by nearly two thirds of the included participants [18]. Less than 50% of the participants knew that the disease can be transmitted from mother to child and slightly above 50% by unsafe sex.…”
Section: Knowledge On Hepatitis B Etiology Transmission Prevention mentioning
confidence: 90%